Women in leadership: impact on liquidity risk and returns in the Chilean stock market - Vásquez-Tejos, Francisco Javier (2025)
This study analyzes the relationship between liquidity risk and stock return volatility, focusing on the influence of female participation on boards of directors and in senior management. The sample includes 69 large Chilean companies listed on the Santiago Stock Exchange between January 2020 and March 2023. Using panel data methodology and five multidimensional indicators of liquidity risk (Relative Quoted Spread, Coefficient of Elasticity of Trading, Share Turnover, Amihud Illiquidity, and Market Efficiency Coefficient), the results show that female representation on boards of directors is significantly associated with reduced liquidity costs and greater market efficiency. In contrast, women in executive roles are linked to higher stock return volatility, suggesting differentiated approaches to risk management. These findings highlight the strategic relevance of gender diversity in corporate governance, providing evidence that inclusive leadership can strengthen market performance and investor confidence in emerging economies.